Influence of muscle volume on jumping performance in healthy male and female youth and young adults - Souhail Bchini; Nadhir Hammami; Taoufik Selmi; Dalenda Zalleg; Anissa Bouassida (BMC, 2023)
Abstract Background Sex differences that appear throughout puberty have a substantial impact on the training process. It remains unclear what effect these sex differences should have on how training programs are planned and performed and what objectives should be established for boys and girls of different ages. This study aimed to investigate the relationship between vertical jump performance and muscle volume based on age and sex. Methods One hundred eighty healthy males (n = 90) and females (n = 90) performed three different types of vertical jumps (VJ): squat jump (SJ), counter movement jump (CMJ), and counter movement jump with arms (CMJ with arms). We used the anthropometric method to measure muscle volume. Results Muscle volume differed across age groups. There were significant effects of age, sex, and their interaction on the SJ, CMJ, and CMJ with arms heights. From the age of 14-15, males exhibited better performances than females, and large effect sizes became apparent in the SJ (d = 1.09, P = 0.04), CMJ (d = 2.18; P = 0.001) and CMJ with arms (d = 1.94; P = 0.004). For the 20-22-year-old age group, there was a significant difference in VJ performance between males and females. Extremely large effect sizes became apparent in the SJ (d = 4.44; P = 0.001), CMJ (d = 4.12; P = 0.001) and CMJ with arms (d = 5.16; P = 0.001). When performances were normalized to the lower limb length, these differences persisted. After normalization to muscle volume, males exhibited better performance when compared to females. This difference persisted only for the 20-22-year-old group on the SJ (p = 0.005), CMJ (p = 0.022) and CMJ with arms (p = 0.016). Among male participants, muscle volume was significantly correlated with SJ (r = 0.70; p < 0.01), CMJ (r = 0.70; p < 0.01) and CMJ with arms (r = 0.55; p < 0.01). Conclusions The results indicate that muscle volume may be one of the major determining factors in sex differences in vertical jumping performance.